Visual spatial attention and spatial working memory do not draw on shared capacity-limited core processes. Issue 5 (May 2020) - Howard, Christina J; Pole, Rebekah; Montgomery, Paulina; Woodward, Amanda; Guest, Duncan; Standen, Bradley; Kent, Christopher; Crowe, Emily M
The extent to which similar capacity limits in visual attention and visual working memory indicate a common shared underlying mechanism is currently still debated. In the spatial domain, the multiple object tracking (MOT) task has been used to assess the relationship between spatial attention and spatial working memory though existing results have been inconclusive. In three dual task experiments, we examined the extent of interference between attention to spatial positions and memory for spatial positions. When the position monitoring task required keeping track of target identities through colour-location binding, we found a moderate detrimental effect of position monitoring on spatial working memory and an ambiguous interaction effect. However, when this task requirement was removed, load increases in neither task were detrimental to the other. The only very moderate interference effect that remained resided in an interaction between load types but was not consistent with shared capacity between tasks—rather it was consistent with content-related crosstalk between spatial representations. Contrary to propositions that spatial attention and spatial working memory may draw on a common shared set of core processes, these findings indicate that for a purely spatial task, perceptual attention and working memory appear to recruit separate core capacity-limited processes.